Comparing alpha-cypermethrin induced dose/gender-dependent responses of lizards in hepatotoxicity and nephrotoxicity in a food chain. (October 2020) - Chen, Li; Wang, Dezhen; Zhou, Zhiqiang; Diao, Jinling
Abstract: Pesticides are proposed as one reason for the worldwide decline in the reptile. Effects of pesticides on food intake and organ toxicity could affect wildlife populations dynamics. To explore the hepatotoxicity of alpha-cypermethrin (ACP) in reptiles, we designed a tri-trophic food chain with three concentrations (0, 2, and 20 mg/kgwet weight ). Although the enzymes changes were similar between male and female lizards, the significant variations in anti-oxidative enzymes' activities, lactic dehydrogenase activities and acetylcholine esterase activities in liver and kidney suggesting that oxidative stress, decreased metabolic ability and neurotoxicity on lizards. The results of hepatic metabolomics showed that ACP could affect amino acid, energy and lipid metabolism on lizards. Comparing with female lizards, there were more significant changes of metabolites in male lizards. The histopathology analysis in the liver (such as hepatic lobule congestion and hepatocyte vacuolation) and kidney (such as renal tubule necrosis and glomerulus necrosis), dose- and gender dependent changes of lesions suggested the functions of organ were damaged. In summary, the reduction of detoxification and elimination capacities of the liver and kidney showed dose/gender-dependent in lizards. Graphical abstract: Image 1 Highlights: ACP could affect amino acid, energy and lipid metabolism in the liver. Oxidative stress occurred in the liver and kidney after dietary exposure ACP. ACP inhibited acetylcholinesterase activities in the liver and kidney. The histopathological lesions occurred in the liver and kidney. Dose/gender-dependent toxicity were observed on lizard.